Ecological Aesthetics of Industrial Product in Urban Design: جاسم خزعل العقيلي -علي غازي مطر (Al-Academy, 2019)
The research addressed the ecological impact of the industrial product as one of the basic aesthetic elements in urban design. The research discussed the nature of the overall ecosystems of the industrial product in urban spaces, and the type of impact they have on each other. The discussion of impacts started from the identification of cognitive and non-cognitive viewpoints in the vision of ecological aesthetics, passing through the inputs of cognitive systems that see that the ecosystem made of the urban space with the existence of the industrial product as one of its constituents, are in fact systems based on functional symmetry between urban space design and the design of the industrial product and the dependence of each other to enrich their aesthetic elements, let alone counting the ecosystem of urban space and industrial product an interactive system that provides a holistic and immersive experience. The researchers analyzed the ecosystems made up of urban space and the industrial product according to specific strategies that allow the formation of a unified ecosystem with distinct aesthetic considerations based on four basic strategies: 1. Bigger effects with less means.2. Unity in diversity. 3. The most sophisticated and still acceptable. 4. Perfect match. The nature of the ecological aesthetics of urban spaces with the presence of industrial product was discussed as an important element in the formation of urban spaces, according to the four previous strategies